2011
DOI: 10.1080/08927022.2011.582111
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculations of redox properties of iron–sulphur protein analogues

Abstract: A central issue in understanding redox properties of iron-sulphur (Fe-S) proteins is determining the factors that tune the reduction potentials of the Fe-S clusters. Studies of redox site analogues play an important role, particularly because individual factors can be examined independently of the environment by combining calculations and experiments of carefully designed ligands for the analogues. For iron-sulphur analogues, our study has shown that broken-symmetry density functional theory gives good energet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 113 publications
(142 reference statements)
1
32
0
Order By: Relevance
“…22-24 Our systematic investigations using B3LYP for [1Fe], 25,26 [2Fe-2S] 27,28,29 and [4Fe-4S] 30,31 analogues are in good agreement with PES detachment energies, while comparisons with the literature show that BP86 functional gives poorer energies. 6 Moreover, our recent studies of [4Fe-4S] proteins have shown that the reduction potentials combining Δ red G in from BS-DFT calculations of gas-phase analogues with Δ red G out from Poisson-Boltzmann (PB) continuum electrostatic calculations of protein crystal structures using partial charges for the redox site from the BS-DFT calculations are in good agreement with experiment. 32 However, these studies also show the conformational dependence of the detachment energies.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…22-24 Our systematic investigations using B3LYP for [1Fe], 25,26 [2Fe-2S] 27,28,29 and [4Fe-4S] 30,31 analogues are in good agreement with PES detachment energies, while comparisons with the literature show that BP86 functional gives poorer energies. 6 Moreover, our recent studies of [4Fe-4S] proteins have shown that the reduction potentials combining Δ red G in from BS-DFT calculations of gas-phase analogues with Δ red G out from Poisson-Boltzmann (PB) continuum electrostatic calculations of protein crystal structures using partial charges for the redox site from the BS-DFT calculations are in good agreement with experiment. 32 However, these studies also show the conformational dependence of the detachment energies.…”
Section: Introductionmentioning
confidence: 72%
“…Calculations of the energetics of the reduction reaction A + e − → A − have been described thoroughly 6 and so are only summarized here. The VDE and VAE (Figure 1b), assuming that most of the coordinates are in their ground vibrational state, are calculated as rightleftVDE[EelecA(A)EelecA(A)]+[Evib,0A(A)Evib,0A(A)]rightleftVDE[EelecA(A)EelecA(A)]+[Evib,0A(A)Evib,0A(A)] where E elec is the calculated electronic energy for the molecule in the superscript at the optimized geometry of the molecule in parenthesis, and E vib,0 is the calculated vibrational energy at 0 K, or ZPE.…”
Section: Methodsmentioning
confidence: 99%
“…Details for the calculations are given elsewhere [18,19] and summarized here. The Δ G in were obtained from BS-DFT calculations at the B3LYP/6-31G(++) S **//B3LYP/6-31G** (energy calculation functional/basis set//geometry optimization functional/basis set) of Fe 4 S 4 (SCH 3 ) 4 1-/2-/3- using the program NWChem [39].…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of this DFT+PB approach is based in part on our extensive testing of the hybrid (rather than LDA) functionals and basis sets [19] used in the BS-DFT calculation of the analog against electrospray ionization - photoelectron spectroscopy (EI-PES) data [2022] of the same analogs in the gas phase. Our DFT calculations also confirm that Δ G in for the iron-sulfur clusters is relatively independent of environment [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation